Trust on awqaf institutions: evidence from Malaysia - Abdul Shukor S.; Johari F.; Abd Wahab K.; Kefeli @ Zulkefli Z.; Ahmad N.; Haji Alias M.; Abdul Rahman A.; Mohd Orip N.M.; Ibrahim P.; Abu-Hussin M.F. (Emerald Group Publishing Ltd., 2024)
Indexed by WOS/Scopus/ERA